2017
DOI: 10.1016/j.advengsoft.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Efficient topology optimization using GPU computing with multilevel granularity

Abstract: This paper proposes a well-suited strategy for High Performance Computing (HPC) of density-based topology optimization using Graphics Processing Units (GPUs). Such a strategy takes advantage of Massively Parallel Processing (MPP) architectures to overcome the computationally demanding procedures of density-based topology design, both in terms of memory consumption and processing time. This is done exploiting data locality and minimizing both memory consumption and data transfers. The proposed GPU instance make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…This partitioning pattern is also demonstrated in Figure 6. The special treatment of halo data on the region boundary has been explored through several GPU computing methods, both the context of the global domain and for local computation [24,23,26]. We next discuss our global memory halo.…”
Section: Implementation 3: Fg Dbd With Memory Coalescingmentioning
confidence: 99%
“…This partitioning pattern is also demonstrated in Figure 6. The special treatment of halo data on the region boundary has been explored through several GPU computing methods, both the context of the global domain and for local computation [24,23,26]. We next discuss our global memory halo.…”
Section: Implementation 3: Fg Dbd With Memory Coalescingmentioning
confidence: 99%
“…Recently, parallelization of topology optimization [103] in the FEM has received interest in the HPC community [104][105][106][107] for elasticity problems. Topology optimization is used to find an optimal design model for particular structures.…”
Section: Some Extraordinary Strategies Favourable To Parallelization mentioning
confidence: 99%
“…Over the last two years, Ram and Sharma [106] and Martínez-Frutos and Herrero-Pérez [107] have successfully exploited the computing power of GPUs to accelerate the topology optimization strategy. Martínez-Frutos et al [104] and Martínez-Frutos and Herrero-Pérez [107] adopted the FG-FEM to accelerate the topology optimization in structural analysis.…”
Section: Some Extraordinary Strategies Favourable To Parallelization mentioning
confidence: 99%
“…Efficient solution schemes and new methods, for example, multiscale finite element methods (Liu, H. et al 2018), multi-resolution TO (Nguyen et al 2012, Groen et al 2017, Liu, C. et al 2018) and others (Guo et al 2016, Li et al 2018, have been developed to reduce the computational cost. Strategies utilizing computer hardware such as parallel computing techniques (Aage et al 2017, Martínez-Frutos et al 2017 have also been proposed. A brief review of various methods and strategies can be found in (Liu, H. et al 2018).…”
Section: Introductionmentioning
confidence: 99%